Fraud Prevention among Internal Auditors: The Roles of Commitment, Integrity, and Internal Control - Dyah Damayanti; Haryanto Damayanti (Value : Jurnal Manajemen dan Akuntansi, 2026)
Persistent corruption cases and high corruption risks in central government institutions indicate that existing prevention mechanisms remain ineffective, highlighting the need to examine behavioral and organizational factors influencing fraud prevention effectiveness. This study examines the effects of organizational commitment and auditor integrity on fraud prevention, with internal control system effectiveness as a moderating variable. This study employs a quantitative approach using survey data collected from 124 auditors out of a total population of 177 auditors at the Inspectorate General of the Indonesian Ministry of Agriculture. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). This study contributes to the literature by examining whether internal control system effectiveness strengthens the behavioral drivers of fraud prevention, thereby providing insight into the interplay between organizational and individual factors. The results indicate that organizational commitment and auditor integrity have a positive and significant effect on fraud prevention. However, internal control system effectiveness does not significantly moderate these relationships, suggesting that formal control systems may not necessarily enhance the influence of these behavioral factors. This finding implies that internal control systems may function more as a baseline governance mechanism rather than as a reinforcing factor in certain organizational settings.